Apolipoprotein E genotype does not moderate the associations of depressive symptoms, neuroticism and allostatic load with cognitive ability and cognitive aging in the Lothian Birth Cohort 1936 - Crook, Zander (PLoS One, 2018)
OBJECTIVES: In this replication-and-extension study, we tested whether depressive symptoms, neuroticism, and allostatic load (multisystem physiological dysregulation) were related to lower baseline cognitive ability and greater subsequent cognitive decline in older adults, and whether these relationships were moderated by the E4 allele of the apolipoprotein E (APOE) gene. We also tested whether allostatic load mediated the relationships between neuroticism and cognitive outcomes. METHODS: We used data from the Lothian Birth Cohort 1936 (n at Waves 1–3: 1,028 [M age = 69.5 y]; 820 [M duration since Wave 1 = 2.98 y]; 659 [M duration since Wave 1 = 6.74 y]). We fitted latent growth curve models of general cognitive ability (modeled using five cognitive tests) with groups of APOE E4 non-carriers and carriers. In separate models, depressive symptoms, neuroticism, and allostatic load predicted baseline cognitive ability and subsequent cognitive decline. In addition, models tested whether allostatic load mediated relationships between neuroticism and cognitive outcomes. RESULTS: Baseline cognitive ability had small-to-moderate negative associations with depressive symptoms (β range = -0.20 to -0.17), neuroticism (β range = -0.27 to -0.23), and allostatic load (β range = -0.11 to 0.09). Greater cognitive decline was linked to baseline allostatic load (β range = -0.98 to -0.83) and depressive symptoms (β range = -1.00 to -0.88). However, APOE E4 allele possession did not moderate the relationships of depressive symptoms, neuroticism and allostatic load with cognitive ability and cognitive decline. Additionally, the associations of neuroticism with cognitive ability and cognitive decline were not mediated through allostatic load. CONCLUSIONS: Our results suggest that APOE E4 status does not moderate the relationships of depressive symptoms, neuroticism, and allostatic load with cognitive ability and cognitive decline in healthy older adults. The most notable positive finding in the current research was the strong association between allostatic load and cognitive decline.